Canadian Labour and Employment Relations - Gunderson, Morley; Taras, Daphne Gottlieb (Pearson Addison Wesley, 2009)
Contents: Canadian labour and employment relations / Daphne G. Taras and Morley Gunderson -- Understanding the unionization decision / Ann C. Frost and Daphne G. Taras -- Labour history and the development of modern capitalism / Richard Marsden -- Unions : membership, structures, actions and challenges / Gregor Murray -- The management of industrial relations / Mark Thompson -- Managing the high-involvement workplace / Anil Verma and Daphne G. Taras -- Social, political, and economic environments / Frank Reid and Rafael Gomez -- Collective bargaining legislation in Canada / Sara Slinn -- The individual employment contract and employment / Geoffrey England -- Collective bargaining : structure, process, and innovation / Richard Chaykowski -- The collective agreement / Anthony Giles and Akivah Starkman -- Strikes and dispute resolution / Morley Gunderson, Bob Hebdon, and Douglas Hyatt -- The grievance arbitration process and workplace / Kenneth Wm. Thornicroft -- Union impact on compensation, productivity, and management of the organization / Morley Gunderson and Douglas Hyatt -- Public-sector collective bargaining / Mark Thompson and Patrice Jalette -- Union-management relations in Québec / Esther Déom and Jean-Noël Grenier with Marie-Pierre Beaumont -- Trade unions and labour relations regimes: international perspectives in a globalizing world / Carla Lipsig-Mummé. Previous eds. published under title: Union-management relations in Canada; Includes bibliographical references and index.
Keywords: Industrial relations -- Canada -- Textbooks